Neither eosinophils nor neutrophils require ATG5‐dependent autophagy for extracellular DNA trap formation. Issue 3 (7th August 2017) - Germic, Nina; Stojkov, Darko; Oberson, Kevin; Yousefi, Shida; Simon, Hans‐Uwe
Summary: The importance of extracellular traps (ETs) in innate immunity is well established, but the molecular mechanisms responsible for their formation remain unclear and in scientific dispute. ETs have been defined as extracellular DNA scaffolds associated with the granule proteins of eosinophils or neutrophils. They are capable of killing bacteria extracellularly. Based mainly on results with phosphoinositide 3‐kinase (PI3K) inhibitors such as 3‐methyladenine (3‐MA) and wortmannin, which are commonly used to inhibit autophagy, several groups have reported that autophagy is required for neutrophil extracellular trap (NET) formation. We decided to investigate this apparent dependence on autophagy for ET release and generated genetically modified mice that lack, specifically in eosinophils or neutrophils, autophagy‐related 5 ( Atg5 ), a gene encoding a protein essential for autophagosome formation. Interestingly, neither eosinophils nor neutrophils from Atg5 ‐deficient mice exhibited abnormalities in ET formation upon physiological activation or exposure to low concentrations of PMA, although we could confirm that human and mouse eosinophils and neutrophils, after pre‐treatment with inhibitors of class III PI3K, show a block both in reactive oxygen species (ROS) production and in ET formation. The so‐called late autophagy inhibitors bafilomycin A1 and chloroquine, on the other hand, were without effect. These data indicate that ET formation occurs independently of autophagy and that the inhibition of ROS production and ET formation in the presence of 3‐MA and wortmannin is probably owing to their additional ability to block the class I PI3Ks, which are involved in signalling cascades initiated by triggers of ET formation. Abstract : The importance of extracellular traps (ETs) in innate immunity is well established, but the molecular mechanisms responsible for their formation remain unclear and in scientific dispute. Here we show that ET formation by both eosinophils and neutrophils occurs independently of autophagy.